Dampak Media Sosial Terhadap Remaja - Aditya Yoga Pratama; Afif Maulana; Ananda Dwi Kurniawan; Syafrilas Sadam; Vicky Maulana; Cucu Hayati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Nowadays, social media is rampant among teenagers, and it has both positive and negative impacts. For example, one positive impact of social media for teenagers is the ability to access information quickly, which broadens their understanding of social issues and increases their awareness of global affairs. However, there are also negative impacts associated with social media use among teenagers. One such negative impact is the dependency on social media, which leads to excessive time spent on these platforms and neglect of more important tasks. Furthermore, social media can adversely affect the mental health of teenagers, as it provides a platform for cyberbullying. This puts teenagers at risk of developing depression, anxiety, and other mental disorders. Therefore, the role of parents is crucial in monitoring their children's social media usage to mitigate the negative impacts. By doing so, they can help teenagers avoid the adverse effects of social media.